Response of Soybean (Glycine max (L.) Merr.) to Micronutrients Zn, Cu, B at Some Dosages of Manure on Latosol Soil - Maya Melati; Fred Rumawas; Justika S Baharsjah; IPG Widjaja Adhi (Forum Pasca Sarjana, 1991)
The experiment was conducted on a Latosol soil at Cikarawang, Bogor, to investigate the response of plant growth, production and seed size of soybean (Glycine mw (L.) Merr.) to applications of chicken manure and micronutrients (Zn, Cu, B). Manure application increased plant growth, yield and seed size. Yield and seed size were highest at the 15 tons manure/ha treatment, without micronutrients. Manure increased P concentrations in leaves and total nutrient uptake, but reduced Ca, Zn, Cu, and B levels. Without manure, the acid soil caused insufficient P availability. Since Ca and Mg were also shown to be in short supply, the soil should be limed with dolomite. This treatment would alleviate N deficiency through better nodule development.